Pengaruh Pendistribusian Zakat Produktif terhadap Kesejahteraan Mustahik pada Baznas Kabupaten Bulukumba - Muhammad Nasri Katman; Nela Novyanti; Rahman Ambo Masse (Department Of Management Zakat and Waqf, 2023)
This study aims to determine the effect of the distribution of productive zakat on the welfare of mustahik at BAZNAS Bulukumba Regency. Using quantitative methods. The population used in this study are productive zakat recipients at the BAZNAS of Bulukumba Regency which were obtained through non-probability sampling techniques and purposive sampling methods. The research data was obtained by distributing questionnaires to 57 mustahik as respondents. Then testing the data either through the classical assumption test, simple linear regression test, hypothesis testing and coefficient of determination test. So it is obtained that productive zakat simultaneously has a significant effect on the welfare of mustahik Baznas Bulukumba Regency. The coefficient of determination is 79.3%. This result shows that the ability of the independent variable (productive zakat) to explain the dependent variable (mustahik's welfare) is 79.3%.